Pengaruh Motivasi Berprestasi dan Penghargaan Terhadap Kepuasan Kerja Dosen IAIN Sultan Amai Gorontalo - Mahmud Domili (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2024)
This research was carried out with the aim of finding out and analyzing the magnitude of the influence of achievement motivation and awards together on the job satisfaction of lecturers at IAIN Sultan Amai Gorontalo. The research approach used is quantitative by collecting data through observation, questionnaires and documentation. The results of the research show that achievement motivation and rewards are consistent simultaneous or together have a significant effect on Job Satisfaction. The amount of contribution can be seen from the coefficient value multiple determination and the award for the conclusion of the research is: simultaneous Achievement Motivation and Rewards play a role in explaining the meaning of a significant positive influence on job satisfaction. Thus the hypothesis which says that simultaneous achievement motivation and reward variables have a significant influence on job satisfaction, while the rest is influenced by other variables such as work environment and leadership style. It is recommended that leaders consider educational factors, skills and expertise of lecturers, balance in rewards, as well as increasing achievement motivation and appreciation for lecturer job satisfaction at IAIN Sultan Amai Gorontalo.